Does National Colorectal Cancer Screening Program Represent Good Value for Money? Results from a Return-on-Investment Model in Vietnam - Nguyen Quynh Anh; Nguyen Thu Ha (SAGE Publishing, 2021)
To provide important evidence for the resource allocation process in Vietnam, this research was conducted to explore the return on investment (ROI) of the national colorectal cancer (CRC) screening program. A decision tree model was designed to estimate the cost and cost savings of a national screening program (ie, providing annual fecal occult blood test [FOBT], following with colonoscopy in case of FOBT positive for the medium-risk group over 50 years old) compared to no screening scenario. This was the first attempt in estimating the ROI of a public health program in Vietnam. Although there was a wide variation due to the uncertainty of the input parameters, especially regarding the coverage of the colorectal cancer screening program in the community, the calculated ROI rates in all different cases were positive, demonstrating that the national colorectal cancer screening program brought benefits to the investment. With a modest coverage of 30% of the population over the age of 50, the corresponding ROI value was 325.4% (95%UI: 321.0; 329.9). The results of this study could be used to advocate for the implementation of a national colorectal cancer screening program in terms of the monetary benefits of investing in the program.